Environmental change in the Western Iberia Upwelling Ecosystem since the preindustrial period revealed by dinoflagellate cyst records. (June 2016) - Ribeiro, Sofia; Amorim, Ana; Abrantes, Fátima; Ellegaard, Marianne
We present the first multi-site study of dinoflagellate cyst records spanning ca. AD 1860–2000 from the west Iberian coast. Our aim was to reconstruct environmental changes in the Western Iberia Upwelling Ecosystem, one of the most biologically productive areas in the world, and an active fishery region. A major shift in cyst assemblages was recorded off the northwestern shelf sector between 1920 and 1950 towards autotrophic dominance, and consisted of a multi-fold increase in total cyst concentrations and cysts of Lingulodinium polyedrum, accompanied by an increase in Protoceratium reticulatum cysts. The observed changes pre-date the industrialization of agriculture in Portugal, and are concomitant with a shift in the North Atlantic Oscillation (NAO) towards negative indices (higher river input) and increasing sea-surface temperatures. The southernmost record, with reduced river- and human influence, showed only minor changes during the 20th century. Here, an increase in Protoperidinioid cysts after the 1980s is related to upwelling intensification. Our study indicates that the main changes recorded in the Western Iberian Upwelling system during the 20th century were driven by regional climate variability (warming, increased water stability and nutrient availability), possibly enhanced by anthropogenic nutrient input from the second half of the century. Our results highlight the complexity of the environmental drivers that may act upon dinoflagellate communities within the same region. The 20th-century environmental change in the Western Iberian Ecosystem has resulted in a shift towards marked autotrophic dominance of dinoflagellate cyst communities, and the northward expansion of species associated with Harmful Algal Blooms.